Sahel workshop welcome address by Dr May-Guri Saethre, DDG R4D IITA - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Research and Delivery Programs for Transforming Agriculture Held at IITA Headquarters, Ibadan, Nigeria, 12-14 March 2019